Leadership without easy answers - Heifetz, Ronald A. (Ronald Abadian), 1951- (Belknap Press of Harvard University Press, 1994)
Drawing on a dozen years of research among managers, officers, and politicians in the public realm and the private sector, among the nonprofits, and in teaching, Heifetz presents clear, concrete prescriptions for anyone who needs to take the lead in almost any situation, under almost any organizational conditions, no matter who is in charge.